2015
DOI: 10.1088/2040-8978/17/12/125012
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic ‘moth-eye’ anti-reflection boundary for graphene plasmons circuits

Abstract: In this paper we propose the biomimetic moth-eye anti-reflection structures on graphene sheet based on transformation optics. The reflections of such structures are investigated by analytical Effective Medium Theory combined with Transfer Matrix Method (EMT/TMM) and numerical Finite Element Method (FEM). Both analytical and numerical methods have shown that the average reflection losses of 1% can be achieved within midinfrared region. Moreover, such performance can be maintained to a very wide incidence angle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The reflection was reduced to less than 1% in the range of 300-1200 nm, profiting from the combined mechanism of light capture and plasma resonance effect. Ren et al [19] demonstrated that the average reflection loss of 1% in the mid infrared region can be obtained based on the graphene plasma circuit with a biomimetic moth-eye structure.…”
Section: Introductionmentioning
confidence: 99%
“…The reflection was reduced to less than 1% in the range of 300-1200 nm, profiting from the combined mechanism of light capture and plasma resonance effect. Ren et al [19] demonstrated that the average reflection loss of 1% in the mid infrared region can be obtained based on the graphene plasma circuit with a biomimetic moth-eye structure.…”
Section: Introductionmentioning
confidence: 99%